Mengungkap Potensi Ritual Merti sebagai Media Dakwah Islam - Joko Subando; Siti Zaida Hanum; Faruq Alhasbi; Muhammad Fathurrahman (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The development of communication technology in modern mass media has shown significant progress. However, traditional media still has its own charm. The existence of traditional media remains popular because it not only serves as a means of conveying messages but also as a manifestation of values of belief and cultural heritage that are worth preserving. Therefore, cultural elements such as the village ritual continue to function as one form of traditional media for spreading religious teachings. In addition to conveying religious messages, this ritual also serves as an outlet for escaping the monotony of rapid modernization. As a result, traditional-based media for spreading religious teachings, such as the village ritual, have persisted to this day and received positive acceptance from society.